Diagnosis and management of skin cancer. (July 2021) - Craythorne, Emma; Nicholson, Prini
Abstract: Skin cancer is the most common cancer in the UK, and incidence rates are continuing to increase. We discuss the common presentations, clinical features, examination techniques, referral guidelines, management and prognosis of both non-melanoma skin cancer (basal cell carcinoma, squamous cell carcinoma) and melanoma.